Perancangan Aplikasi Web E-Commerce Penjualan Produk Asuransi Kendaraan Terintegrasi Api Midtrans Menggunakan Metode Extreme Programming (Studi Kasus: Pt. Komet Bersama Indonesia) - Arief Setiawan; Maulana Ardhiansyah (INFORMATIKA, 2022)
PT. Komet Bersama Indonesia is a company that sells vehicle insurance products located on Jl. KH Hasyim, Ashari No. 11C, Central Jakarta. The current running system has several drawbacks. Weaknesses such as the promotion system are still through the closest people or relatives, recording transactions manually, when performing data redundancy when employees are recording, the transaction process is still carried out at the time of marketing. The purpose of this study is to produce an e-commerce website application that has been integrated with the Midtrans payment gateway. It is hoped that with e-commerce customers can find out information about insurance product details more quickly and easily. This study uses the Extreme Programming (XP) method as a development method which has several stages, namely planning, designing, coding and testing. The system testing method used is the Black Box method. Based on the results of system implementation and testing, it can be said that the e-commerce website application for selling vehicle insurance products can assist customers or users in obtaining information about details and prices of vehicle insurance products quickly and easily.